2005
DOI: 10.1093/jac/dki135
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular analysis of extended-spectrum β-lactamase-producing Proteus mirabilis in Hong Kong, 1999–2002

Abstract: Our findings indicate the emergence of CTX-M enzymes among P. mirabilis in Hong Kong. More ESBL screening of this species is required to improve their recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…A diversity of ESBLs such as TEM-derived mutants was reported to be produced by P. mirabilis in Europe (Bonnet et al, 1999;Luzzaro et al, 2001;Biendo et al, 2005). CTX-M-2-, CTX-M-3-, CTX-M-13-and CTX-M-14-producing P. mirabilis has been reported in Hong Kong, Taiwan and Japan (Nagano et al, 2003;Ho et al, 2005;Wu et al, 2006). These data indicate a geographical feature of ESBL-producing P. mirabilis, with TEM types in Europe and CTX-M types in Eastern Asia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A diversity of ESBLs such as TEM-derived mutants was reported to be produced by P. mirabilis in Europe (Bonnet et al, 1999;Luzzaro et al, 2001;Biendo et al, 2005). CTX-M-2-, CTX-M-3-, CTX-M-13-and CTX-M-14-producing P. mirabilis has been reported in Hong Kong, Taiwan and Japan (Nagano et al, 2003;Ho et al, 2005;Wu et al, 2006). These data indicate a geographical feature of ESBL-producing P. mirabilis, with TEM types in Europe and CTX-M types in Eastern Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Uniquely, the species isolated in Japan possessed the CTX-M-2 enzyme frequently and predominantly in the Enterobacteriaceae. Previous studies have reported that ESBL-producing P. mirabilis in hospitals always encoded additional b-lactamase genes (Ho et al, 2005;Wu et al, 2006), with the exception of nosocomial outbreaks by ESBL-producing clonal strains (Nagano et al, 2003;Kim et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Class A β-lactamases from the TEM group have occurred at a particularly high frequency; in many surveillance studies, they have been identifi ed as the resistance determinants most frequently encountered (2)(3)(4)(5)(6)(7)(8)(9). The fi rst bla TEM allele, bla TEM-1 , is a plasmidic allele that was fi rst isolated in 1963 (10,11).…”
mentioning
confidence: 99%
“…An obvious prediction for ESBL bla TEM alleles is that they would either co-occur with bla TEM-1 or replace it as the most frequently encountered allele in environments where cephalosporins are heavily used. However, neither of these patterns has been observed among clinical populations of microorganisms, and bla TEM-1 is still the most commonly occurring allele in many microbial populations where cephalosporin resistance has been selected for (1,3,9,12,13,17,19,20,30,34). The high frequency of bla TEM-1 in microbial populations is counterintuitive, because the alleles descended from bla TEM-1 confer both the advantageous cephalosporin resistance phenotypes and the ancestral penicillin resistance phenotype, which should promote their fixation in microbial populations.…”
mentioning
confidence: 99%